Assessing cost-effectiveness of alternative bus technologies: Evidence from US transit agencies. (April 2023) - Avenali, Alessandro; Catalano, Giuseppe; Giagnorio, Mirko; Matteucci, Giorgio
Highlights: Data-driven economic assessment of alternative power technologies for transit buses. Life cycle social cost model as a tool for policy-making on alternative bus powertrains. High purchase costs and limited battery range hinder electric bus deployment. Congested urban routes are the most suitable for electric buses. Abstract: This paper aims to analyze overall economic and environmental performances of alternative bus powertrains by focusing on U.S. active fleets in different urban contexts. We define a life cycle cost model related to bus technologies by referring to real-world data of 256 transport operators, which provide more than 80% of total vehicle revenue miles produced by urban transit mode across the U.S. in 2019. The proposed method includes some service parameters that significantly affect the supply cost (e.g., service speed, annual mileage), on which we perform scenario and sensitivity analysis. Results show that electric buses are cost-competitive in large cities and metropolises, where urban bus routes are characterized by a high level of congestion, high service frequency, and the highest marginal impact of harmful emissions. In towns and suburban areas, where bus routes are longer and faster, full electric technology still faces both economic and technical barriers.